Origination The Geographies of Brands and Branding - Pike, Andy (RGS-IBG Book Series, 2015)
Origination: The Geographies of Brands and Branding offers innovative theoretical and conceptual frameworks relating to the ways that actors create meaning and value in commodity brands and branding through processes of geographical association. Provides innovative conceptualization and theorization to facilitate an understanding of the geographical dimensions of brands and branding Challenges current interpretations of brands as vehicles of homogenization in globalization Establishes the theoretical and conceptual foundations of a more geographically sensitive approach through rigorous empirical examination of the under-researched geographical differentiation of commodity brands and branding Presents innovative new research and analysis of the socio-spatial biographies of the Newcastle Brown Ale, Burberry and Apple brands Forges strong new connections between political and cultural economy approaches within geography Provides a distinctive and incisive conceptual and theoretical framework capable of engaging other branded commodities and their branding in other times and places